2015
DOI: 10.1074/jbc.m114.630681
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Dopamine D3 Receptor Quaternary Structure

Abstract: Background: The dopamine D3 receptor can form dimers/oligomers, but the molecular basis for this is poorly defined.Results: Molecular modeling, mutagenesis, and analysis of inactive state receptor crystal structures allowed assessment of models of receptor organization.Conclusion: The dopamine D3 receptor can assume different dimeric and a rhombic tetrameric arrangements.Significance: These findings provide understanding of the molecular basis of D3 receptor quaternary structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…2 ) as well as by recent experimental data for a close homolog of the D 2 receptor, namely the D 3 receptor dimer [ 42 ]. Marsango et al [ 42 ] used molecular modeling, mutagenesis and analysis of inactive state receptor crystal structures to indicate that D 3 monomers can interact with each other via at least two distinct interfaces: the first comprising residues from transmembrane domains TM1 and TM2 along with those from TM7, and a second involving transmembrane domains TM4 and TM5. Moreover, Guitart et al [ 43 ] also reported that the D 1 receptor TM5 peptide was also able to reduce D 1 –D 1 receptor complementation.…”
Section: Resultsmentioning
confidence: 95%
“…2 ) as well as by recent experimental data for a close homolog of the D 2 receptor, namely the D 3 receptor dimer [ 42 ]. Marsango et al [ 42 ] used molecular modeling, mutagenesis and analysis of inactive state receptor crystal structures to indicate that D 3 monomers can interact with each other via at least two distinct interfaces: the first comprising residues from transmembrane domains TM1 and TM2 along with those from TM7, and a second involving transmembrane domains TM4 and TM5. Moreover, Guitart et al [ 43 ] also reported that the D 1 receptor TM5 peptide was also able to reduce D 1 –D 1 receptor complementation.…”
Section: Resultsmentioning
confidence: 95%
“…However, in many of these studies, the point mutants did not eliminate energy transfer completely, which was interpreted as evidence of higher-order oligomers and multiple dimerization interfaces. 2630 The difficulty with BRET and FRET studies is that they can be overly sensitive to weak and transient interactions and potentially overestimate the extent of dimerization. This interpretation was supported by data from several assays that are sensitive to dimer lifetimes.…”
mentioning
confidence: 99%
“…Different strategies have been used to map the GPCR dimer interface and its functional significance. These strategies include: (i) structure-based molecular modeling to predict residues potentially involved in dimer formation (42)(43)(44); (ii) cysteine mutagenesis of amino acids predicted to be involved in formation of the dimer followed by cross-linking, which successfully mapped several amino acids at the dimer interface of opsin, dopamine D2, and serotonin 5HT2c receptors (45)(46)(47); and (iii) disruption of the dimer interface by mutation of certain dimer-contacting residues (48,49) or with synthetic peptides derived from selected TM domains, resulting in specific alterations of receptor function, which for example was demonstrated for CXCR4 and formyl peptide receptors targeting TM4 (50,51) and for ␤ 2 AR and leukotriene B4 (BLT1) receptors targeting TM6 (52,53). However, TM peptides corresponding to TM6 and TM7 of the cholecystokinin receptor inhibited receptor dimerization without altering its function, as assessed by ligand binding and agonist-stimulated intracellular calcium concentration assays (25).…”
mentioning
confidence: 99%